PL01.1 Antimicrobial Resistance in Neisseria Gonorrhoeae and Possible Emergence of Untreatable Gonorrhoea: How, When and Essential Actions?. (13th July 2013) - Unemo, M
Abstract : The WHO estimated 106 million gonorrhoea cases in 2008 globally and antimicrobial resistance (AMR) in Neisseria gonorrhoeae is a major public health concern that compromises effective treatment and disease control efforts worldwide. The new superbug Neisseria gonorrhoeae has retained high-level resistance to antimicrobials previously recommended for first-line treatment and, recently, the first extensively drug-resistant (XDR) gonococcal strains with high-level resistance to the extended-spectrum cephalosporin (ESC) ceftriaxone, the last remaining option for first-line empiric monotherapy of gonorrhoea, were reported. This is of grave concern and it is feared that gonorrhoea may become untreatable under certain circumstances. In this talk, with particular emphasis on ESCs the evolution, origin, emergence and spread of AMR and genetic AMR determinants; their relevance and effects (including interplay and epistasis) on AMR and biological fitness of gonococcal strains; gonococcal population dynamics and international spread of biologically "successful" AMR gonococcal clones; genetic AMR detection methods; current situation regarding verified treatment failures with ESCs, and suggested future treatment options will be discussed. Essential actions to combat the emergence of multidrug resistant and possibly untreatable gonorrhoea will also be highlighted, such as implementing the WHO Global Action Plan and national or regional action/response plans, e.g., the ECDC Response plan for the European Union and the CDC Response Plan for the USA; enhancing surveillance of gonococcal antimicrobial resistance, treatment failures and antimicrobial use/misuse; and improving prevention, early diagnosis and treatment of gonorrhoea to reduce the gonorrhoea burden. All these responses will be valuable in detaining the global spread of AMR, however, in a longer term not sufficient to prevent the emergence and spread of potentially untreatable gonorrhoea. Few promising new antimicrobials are in sight, and it is essential to promptly focus research on timely development of novel effective drugs for treatment of gonorrhoea, and ideally, a vaccine.